Analisis, Perancangan Layanan Terpadu e-Mall multi_mitra teknologi SOA menghadapi PandemiCOVID-19 - kartini kartini; Riya Widayanti (Universitas Lampung, 2020)
The progress of the development of information technology, communication and SOA (Service Oriented Architecture) that is very fast making all activities of aspects of human life must follow. Especially creating long distance shopping and transactions, one way to avoid the crowds and chaos of people when conditions (epidemics that are simultaneously contagious everywhere, covering large geographical areas) the COVID-19 pandemic. Among them are business, business, education, and other activities. Constraints developing applications, it is very difficult and expensive and requires a long time due to differences in platforms between applications and limited access to the server for the security of the server itself. SOA can solve this problem, can make existing programs become service oriented. This can be done with programs that have been built in a modular manner so that it is enough to only add web services techniques in them. Then a service interface is created without changing the logic of the program. Thus the testing is sufficient on the interface, while the function / logic in it does not need to be tested again because it does not change. SOA integrates and accelerates Multi-Partner business processes, all of which can improve efficiency in all fields. Based on this fact this research was conducted. The research method begins with a literature study, and documentation of related journals as a reference source for analysis. Then proceed with direct observation, conducting interviews with several Mall partners; store owner, banks, residents / customers in the Mall (the author is not allowed to mention the name of the store owner, customer name, name of the store owner, and the name of the Mall) to get the required data Modeling the system design process of the Unified Modeling Language, Enterprise Architect and tenology used by SOA. The system development method uses Prototype. The end result of this research (study) is expected to be used by related parties in developing remote transactions and other parties interested in SOA.